2012
DOI: 10.1186/1748-717x-7-18
|View full text |Cite
|
Sign up to set email alerts
|

A national survey of the availability of intensity-modulated radiation therapy and stereotactic radiosurgery in Canada

Abstract: BackgroundThe timely and appropriate adoption of new radiation therapy (RT) technologies is a challenge both in terms of providing of optimal patient care and managing health care resources. Relatively little is known regarding the rate at which new RT technologies are adopted in different jurisdictions, and the barriers to implementation of these technologies.MethodsSurveys were sent to all radiation oncology department heads in Canada regarding the availability of RT equipment from 2006 to 2010. Data were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 31 publications
1
17
1
Order By: Relevance
“…Our results show that all NZ centres had IMRT/VMAT capabilities, in keeping with international trends reporting increased adoption of these techniques over time. 10,12 We found a high uptake of IMRT/ VMAT in H&N and GU malignancies and selective use in other sites, similar to the trend reported in an Australian survey. 10 The strong utilization of IMRT/VMAT for H&N and GU sites is supported by the literature, with improved outcomes in these patients.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our results show that all NZ centres had IMRT/VMAT capabilities, in keeping with international trends reporting increased adoption of these techniques over time. 10,12 We found a high uptake of IMRT/ VMAT in H&N and GU malignancies and selective use in other sites, similar to the trend reported in an Australian survey. 10 The strong utilization of IMRT/VMAT for H&N and GU sites is supported by the literature, with improved outcomes in these patients.…”
Section: Discussionsupporting
confidence: 84%
“…There was a broad range of number of staff members per centre for ROs (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15), physicists (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15) and radiation therapists .…”
Section: Demographicsmentioning
confidence: 99%
“…For example, a survey of all cancer centres in Canada showed that the proportion of centres offering IMRT rose from 37% to 87% between 2006 and 2010. 22 In the UK, it increased from 46% to 81% between 2007 and 2012. 23 24 The key indicator for patients is access to this treatment when needed: it has been estimated that about 33% of radically treated patients should receive IMRT.…”
Section: Intensity Modulated Radiotherapy (Imrt)mentioning
confidence: 99%
“…Regular audits in the literature attempt to track trends in availability of radiation therapy (RT) technology such as intensity‐modulated radiotherapy (IMRT) from a range of countries . There is a big difference, however, between the availability of resources and actual usage with the resource‐hungry nature of commissioning in particular affecting implementation and usage of the available technology and equipment .…”
Section: Introductionmentioning
confidence: 99%